The The Holocene – Present Shoreline Migration off Thai Binh – Nam Dinh in Relation to Evolution of Deltaic Lobes and History of the So River - Thi Thanh Nhan, Tran; Ghi, Tran; Ngoc Dien, Tran; Xuan Thanh, Dinh; Thi Dung, Tran; Thi Phuong Thao, Nguyen; Xuan Truong, Dinh; Manh Tuan, Do; Dinh Lam, Doan (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 4, 2018)
Abstract: The Holocene – Present shoreline migration of Thai Binh - Nam Dinh has occurred in different situations and has been controlled by evolution of deltaic lobes and history of the So River. The shoreline of Ba Lat River mouth is now characterized by strongaggradation while the Hai Hau shoreline is experiencing rapid erosion process, leading to serious damage of the coastal works. In this paper, the authors will answer the aforementioned questions based on the study results of shoreline variation off Thai Binh and Nam Dinh, as well ad the linkage to the evolution of the So River during the Holocene - Present Period. During the aggradation and seaward extension of the Red River Delta, 8 successive deltaic lobes have been formed into a fan-shape formation between 2500 yr. BP shoreline and present shoreline. The Red River trunk has flown across Hai Hau and connected to the sea via Ha Lan Estuary before 1787. However, a disaterous flood occurred in 1787 that destroyed the river bank and made paleo-Red River narrower. Since that time the paleo-Red River became the So River today while the main Red River channel migrated between Nam Dinh and Thai Binh Provinces and finally follows out via Ba Lat Mouth that used to be a minor outlet. Although the river channel was narrowed and sediment budget was decreased, the coastal zone in Hai Hau has continued to extend outward at a rate of ~30m/yr. The coast in Hai Hau has been eroded at a rate of ~19.5m/yr. since a hydraulic dam was built in the So River in Ngo Dong. It means that the rapid erosion off Hai Hau coast was likely caused by the historical food in 1787 and construction of hydraulic dam in 1960. In order to present the coast from erosion, it is necessary to remove the Ngo Dong Dam and enlarge the So River trunk. References [1] Trần Đức Thạnh, Nguyễn Hữu Cử, Nguyễn Đức Cự, và nnk. Tình trạng và nguyên nhân xói lở, bồi tụ ven bờ châu thổ sông Hồng. Tạp chí Tài nguyên và Môi trường biển. Tập III. [2] Hoàng Ngọc Kỷ, 1989. Địa tầng và những nét lớn của lịch sử phát triển địa chất miền Bắc Việt Nam trong Đệ tứ. Tóm tắt luận án PTS Khoa học Địa lí – Địa chất; 21tr. Hà Nội: Đại học Tổng hợp Hà Nội. [3] Ayako Funabiki, Yoshiki Saito, Vu Van Phai, Nguyen Hieu and Shigeko Haruyama, 2012. Natural levees and human settlement in the Song Hong (Red River) delta, northern Vietnam. The Holocene 22(6) 637 –648. [4] Ngô Quang Toàn, 1995. Đặc điểm trầm tích và lịch sử phát triển các thành tạo Đệ tứ ở phần đông bắc đồng bằng Sông Hồng. Luận án TS Khoa học Địa lí – Địa chất; 20tr, Đại học Tổng hợp Hà Nội. [5] Tran Nghi, Mai Trong Nhuan, Chu Van Ngoi, Nguyen Van Dai, Dinh Dinh Xuan Thanh, Nguyen Dinh Nguyen, Nguyen Thanh Lan, Dam Quang Minh and Ngo Quang Toan, 2003. GIS and image analysis to study the process of late Holocene sedimentary evolution in Balat River Mouth, Vietnam. Geoinformatics, vol. 14, no. 1, 43-48. [6] Tran Nghi, Mai Trong Nhuan, Chu Van Ngoi, P. Hoekstra, Utrecht, TJ. Van Weering, J.H. Van Denbergh, Dinh Xuan Thanh, Nguyen Dinh Nguyen, Vu Van Phai, 2002. Holocene sedimentary evolution, geodynamic and anthropogenic control of the Balat river mouth formation (Red River-delta, northern Vietnam). Z. geol. Wiss., Berlin 30, 3: 157 – 172. [7] Trần Nghi, Đinh Xuân Thành và nnk., 2000. Quá trình tích tụ trầm tích Đệ tứ của đáy Sông Hồng trong mối quan hệ với hoạt động nhân sinh. Tuyển tập báo cáo hội thảo khoa học đánh giá tác động của quá trình xói mòn tại lưu vực Sông Hồng. Lưu trữ Viện HLKH&CNVN. Tr. 124-151. [8] Trần Nghi, Ngô Quang Toàn, 1991. Đặc điểm các chu kỳ trầm tích và lịch sử tiến hóa địa chất Đệ tứ đồng bằng Sông Hồng, Tạp chí địa chất (số 206-207), tr. 65-69. [9] Trần Nghi, Nguyễn Thế Tiệp, 1993. Đặc điểm trầm tích trong mối tương tác thạch động lực của vùng tiền châu thổ Sông Hồng. Tạp chí các khoa học về Trái đất, số 1, tr. 26-32. [10] Vũ Quang Lân, 1999. Các mặt cắt địa chất chủ yếu của hệ tầng Hải Hưng vùng đồng bằng Sông Hồng. Tạp chí địa chất, số 251, tr. 9-13. [11] Do Minh Duc, Mai Trong Nhuan, Chu Van Ngoi, Tran Nghi, Dao Manh Tien, Tj. C.E. van Weering, G.D. van den Bergh, 2007. Sediment distribution and transport at the nearshore zone of the Red River delta, Northern Vietnam. Journal of Asian Earth Sciences 29, 558–565. [12] Trần Đức Thạnh, Đinh Văn Huy, Trần Đình Lân, 1996. Đặc điểm phát triển của vùng đất bồi ngập triều ven bờ châu thổ Sông Hồng. Tạp chí các Khoa học về Trái đất, số 1, tr. 50-59. [13] Vũ Cao Minh, Nguyễn Khắc Nghĩa, Nguyễn Huy Thịnh, 2006. Biến động cửa Ba Lạt, cửa Hà Lạn trong thời kỳ cận đại và ảnh hưởng của chúng tới diễn biến bồi tụ xói lở khu vực Hải Hậu - Nam Định. Tạp chí KH&CN Thủy lợi Viện KHTLVN. [14] Susumu Tanabe, Yoshiki Saito, Quang Lan Vu, Till J.J. Hanebuth, Quang Lan Ngo, Akihisa Kitamura, 2006. Holocen Evolution of the Song Hong (Red River) delta system, Northen Vietnam. Sedimentary Geology, 187, 29-61. [15] Doãn Đình Lâm, 2003. Tiến hóa trầm tích Holocen châu thổ Sông Hồng. Luận án tiến sĩ địa chất, ĐHQGHN. [16] Trần Nghi, Nguyễn Thị Tuyến, Đinh Xuân Thành, Nguyễn Đình Nguyên, Trần Thị Thanh Nhàn, Nguyễn Đình Thái, Nguyễn Thị Huyền Trang. Đường bờ cổ và ranh giới chéo các miền hệ thống trầm tích Pleistocen muộn-Holocen khu vực Bắc bộ và Bắc trung bộ. Tạp chí Địa chất, loạt A, số 358, 9-10/2016, Tr. 1-13. [17] Susumu Tanabe, Kazuaki Hori, Yoshiki Saitoc, Shigeko Haruyamad, Van Phai Vu, Akihisa Kitamura, 2003. Song Hong (Red River) delta evolution related to millennium-scale Holocene sea-level changes. Quaternary Science Reviews 22, 2345–2361. [18] Nguyễn Quang Miên, Lê Khánh Phồn, 2000. Some results of C14 dating in investigation on Quaternary geology and geomorphology in Nam Định - Ninh Bình area, Việt Nam. J. Geology, B/15: 106-109. Hà Nội. [19] Trần Nghi, 2012. Trầm tích học. Nhà xuất bản ĐHQGHN. [20] Trần Nghi, Nguyễn Thị Tuyến, Đinh Xuân Thành, Nguyễn Đình Nguyên, Trần Thị Thanh Nhàn, Nguyễn Đình Thái, Nguyễn Thị Huyền Trang, Lê Viết Chuẩn, Nguyễn Hoàng Long. Đặc điểm tướng đá – cổ địa lý Pleistocen muộn – Holocen khu vực cửa sông Ba Lạt. Tạp chí Khoa học và Công nghệ Biển; Tập 17, Số 1; 2017; Tr. 23-34. [21] Vũ Văn Tiếu, 2017. Lịch sử Làng Gòi-Sa Châu Ghi chú: [22] Vũ Văn Tiếu: Cháu nội ông Tổng Vũ Đình Khang viết tiếp từ năm 1956 đến năm 2017 [23] Cụ Chánh Vũ Đình Nam (Đời thứ 8 của cụ Đồ Đáo) dịch từ chữ Hán ra chữ quốc ngữ. [24] Cụ Tổng Vũ Đình Khang con trai cụ Chánh Vũ Đình Nam viết tiếp từ năm 1924 đến năm 1956.